2018
DOI: 10.2147/clep.s159405
|View full text |Cite
|
Sign up to set email alerts
|

Noncommunicable disease and multimorbidity in young adults with cerebral palsy

Abstract: PurposeIndividuals with cerebral palsy (CP) are at increased risk for frailty and chronic disease due to factors experienced throughout the lifespan, such as excessive sedentary behaviors and malnutrition. However, little is known about noncommunicable diseases (NCDs) and multimorbidity profiles in young adults with CP. The study objective was to compare NCD and multimorbidity profiles between young adults with and without CP.MethodsA clinic-based sample of adults (18–30 years) with (n=452) and without (n=448)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
156
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 100 publications
(159 citation statements)
references
References 42 publications
3
156
0
Order By: Relevance
“…Therefore, the men with CP >70 years with public insurance may be abnormally healthier than what would be expected for a CP diagnosis at that age. Nevertheless, our prevalence trends are concordant with previous research in southeast Michigan showing that young adults (18 to 30 years) with CP have a musculoskeletal morbidity profile that is 10 times higher than young adults without CP, with the trend of musculoskeletal morbidity becoming even more prevalent with older age …”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the men with CP >70 years with public insurance may be abnormally healthier than what would be expected for a CP diagnosis at that age. Nevertheless, our prevalence trends are concordant with previous research in southeast Michigan showing that young adults (18 to 30 years) with CP have a musculoskeletal morbidity profile that is 10 times higher than young adults without CP, with the trend of musculoskeletal morbidity becoming even more prevalent with older age …”
Section: Discussionsupporting
confidence: 91%
“…Covariates were selected based on their relevance to adults with CP, fracture, and availability in the administrative claims database . Sociodemographic and socioeconomic variables included age, sex, ethnic group, and education level.…”
Section: Methodsmentioning
confidence: 99%
“…Sociodemographic and socioeconomic variables included age, sex, ethnic group, and education level. We have previously reported that adults with CP had a higher prevalence of cardiometabolic diseases and osteoporosis compared with adults without CP . Cardiometabolic diseases and osteoporosis are associated with skeletal fragility in the non‐CP population, and were therefore included as covariates grouped in the following categories: ischemic heart disease (eg, atherosclerotic heart disease); cerebrovascular disease (eg, cerebral infarction); hypertensive and other cardiovascular disease (eg, hypertension, heart failure); type 2 diabetes; and osteoporosis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations